Factors Affecting Patient Safety Incidents In Datu Beru Takengon Regional Hospital In 2021 - Indra Lutfi; Arifah Devi Fitriani; Meppeaty Nyorong (Institute of Computer Science (IOCS), 2022)
Patient safety is the most important global issue today where there are now many reports of patient demands for medical errors that occur in patients. The report of the Committee for Quality Improvement and Patient Safety (PMKP) in 2020 at the Datu Beru Takengon Regional General Hospital showed that there were 15 safety incidents. This research is a quantitative research with a cross sectional study design, which is a measurement of the dependent variable and the independent variable of the relationship between nurse characteristics (age, gender, education, years of service and unit tenure), organizational factors, teamwork factors, work environment factors, individual factors with the dependent variable of patient safety and using a survey method. From the results of the study, the most dominant factor influencing patient safety was the teamwork factor variable p 0.000 <0.05 and 95% CI 0.014-0.244 meaning that the teamwork factor had an effect on patient safety at Datu Beru Takengon General Hospital. In the study, there was a significant influence on the occurrence of patient safety incidents, whether it was from individual nurses such as age, education, years of service, work units, organizational factors, teamwork factors, environmental factors and individual factors. The conclusion of this study that the teamwork factor is a more influential variable than the others in the occurrence of patient safety incidents in the inpatient unit. It is hoped that the management of is more serious in establishing quality improvement and patient safety (PMKP).